Chrysin Increases the Therapeutic Efficacy of Docetaxel and Mitigates Docetaxel-Induced Edema. (December 2017) - Lim, Hyun-Kyung; Kim, Kyoung Mee; Jeong, Seong-Yun; Choi, Eun Kyung; Jung, Joohee
Docetaxel (DTX) is an effective commercial anticancer agent for chemotherapy in non–small cell lung cancer (NSCLC), breast cancer, gastric cancer, and prostate cancer, but its adverse effects including edema, neurotoxicity, and hair loss limit its application. To improve the chemotherapeutic efficacy of DTX and reduce adverse effects, combination therapy is one of the alternative methods. So chrysin, which has various biological activities including anticancer effects, was considered. In vitro, the combination of chrysin and DTX was investigated in A549 cells. Increased cytotoxicity, suppressed cellular proliferation, and induced apoptosis were observed with posttreatment of chrysin following DTX treatment. In vivo, chrysin enhanced the tumor growth delay of DTX and increased DTX-induced apoptosis in the A549-derived xenograft model. Furthermore, chrysin prevented DTX-induced edema in ICR mouse. These results indicated that chrysin strengthened the therapeutic efficacy of DTX and diminished the adverse effect of DTX, suggesting chrysin could be exploited as an adjuvant therapy for NSCLC.